Estimating the size of a potential palliative care population - Rosenwax, Lorna; McNamara, B.; Blackmore, A.; Holman, C. (2005)
Objectives: To develop a method for estimating the population who could potentially benefit from receiving palliative care in the last year of their lives, and then apply the estimates to the Western Australian population to ascertain characteristics of these people.Methods: Three estimates of the potential palliative care population, Minimal, Mid-range and Maximal, were developed through focus groups, interviews and the literature. These estimates were applied to the cohort of people who died in Western Australia between 1 July 2000 and 31 December 2002 by linking death records with hospital morbidity data through the Western Australian Data Linkage System. Results: Between 0.28% and 0.50% of people in the Western Australian population in any one year could potentially benefit from palliative care, many of whom die from conditions other than neoplasms. While neoplasms accounted for 59.5% of all underlying causes of deaths in the Minimal Estimate, heart failure (21.0%), renal failure (9.8%), chronic obstructive pulmonary disease (9.6%), Alzheimer’s disease (4.0%), liver failure (3.2%), Parkinson’s disease (1.3%), motor neurone disease (0.9%), HIV/AIDS (B/0.01%) and Huntington’s disease (B/0.01%) accounted for other conditions in this estimate. The study was expanded to include Mid-range and Maximal Estimates. Characteristics of the Western Australian population in these three estimates are described. Conclusions: Unlike traditional palliative care estimates that focus on malignant disease, this study included nonmalignant conditions in a set of three estimates of a potential palliative care population. By using population-based data to describe characteristics of people who compose palliative care populations, these results offer a tool for planning equitable healthcare services.